DNA Damage Inducible Protein 1 is Involved in Cold Adaption of Harvested Cucumber Fruit - Wang, Bin; Wang, Guang; Zhu, Shijiang (Frontiers in Plant Science, 2020)
Chilling stress can cause cellular DNA damage, affecting the faithful transmission of genetic information. Cold acclimation enhances chilling tolerance, but it is not clear that the process of cold adaption involves DNA damage responses, as cold acclimation does not form real chilling stress. Here we showed with cucumber fruit that pre-storage cold acclimation (PsCA) reduces chilling injury and upregulates DNA damage inducible protein1 (CsDDI1), suggesting that the chilling tolerance induced by cold acclimation involves CsDDI1 transcription. Application of nitric oxide (NO), abscisic acid (ABA) or H2O2 biosynthesis inhibitor before PsCA treatment downregulates CsDDI1 and aggravates chilling injury, while H2O2 generation inhibition plus exogenous NO or ABA application before PsCA treatment restores chilling tolerance, but does not restore CsDDI1 expression, suggesting H2O2 plays a crucial role in triggering cold adaption. CsDDI1 overexpression Arabidopsis lines show faster growth, stronger chilling tolerance, lower reactive oxygen species levels, enhanced catalase and superoxide dismutase activities and higher expression of nine other Arabidopsis defense genes under chilling stress, suggesting CsDDI1 strengthens defenses against chilling stress by enhancing antioxidant defense system. Taken together, CsDDI1 positively regulates chilling tolerance induced by cold acclimation in cucumber. In addition, H2O2 is involved in initiation of cold acclimation. While CsDDI1 upregulation requires H2O2 as a key signaling molecule, the upregulation of CsDDI1 activates an antioxidant system to reduce biotoxic accumulation of H2O2 and helps in DNA repair .